2012
DOI: 10.1080/03057240.2012.677600
|View full text |Cite
|
Sign up to set email alerts
|

From prejudice to reasonable judgement: integrating (moral) value discussions in university courses

Abstract: The findings revealed that 79 percent of the managers and more than half of the lecturers though that research should be a preoccupation of the hogescholoen. Both the lecturers and the managers gave higher ratings to research for the purpose of enlarging the external orientation of the institution and solving practical issues than to the development of new theory. These findings, therefore, indicate only a modest tendency toward academic drift. (52 ref)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…In the previous section, we have concluded that science is not value free. However, students often automatically start reasoning from a value-free point of view (Aalberts, Koster and Boschhuizen 2012;Koster and Boschhuizen 2018;Fisher and Moody 2002;King and Kitchener 2004). Usually students suppose that science is about the facts and only about the facts.…”
Section: Calls It?mentioning
confidence: 99%
See 3 more Smart Citations
“…In the previous section, we have concluded that science is not value free. However, students often automatically start reasoning from a value-free point of view (Aalberts, Koster and Boschhuizen 2012;Koster and Boschhuizen 2018;Fisher and Moody 2002;King and Kitchener 2004). Usually students suppose that science is about the facts and only about the facts.…”
Section: Calls It?mentioning
confidence: 99%
“…The course shows the complex relation between science and values in the scientific discipline of the students, but usually none of this is seen by them to apply directly to the role of values and convictions regarding their own scientific practices. Due to the way textbooks teach them to think about science, they still think of themselves as value-free agents of science (Aalberts, Koster and Boschhuizen 2012). During their studies, however, students become themselves more and more involved in the process of scientific research, and this process is thus (possibly unnoticed) influenced by epistemic and perhaps even non-epistemic values.…”
Section: Values: From Awareness To Self-awarenessmentioning
confidence: 99%
See 2 more Smart Citations
“…Using strategies such as dilemma orientated discussion groups (Aalberts, Koster and Boschhuizen, 2012), problem or inquiry based learning (Clouston and Whitcombe 2005) and appreciative inquiry (Roberts and Machon 2015) to encourage awareness and ethical decision-making (Cranton 2006;Mezirow 2003) can all aid to achieve an understanding of a principled and ethically constructed service. However, research in practice settings, an integral part of all professionally related health and social care programmes, has found that students, even at this nascent level of development, can become acculturated to the embedded cultures of speed, pressure and discharge before care and compassion (Maben, Latter and Clark 2007;Reiss 2010).…”
Section: The Principlesmentioning
confidence: 99%